Characterization of demethylating DNA glycosylase ROS1 from Nicotiana tabacum L. - D. V. Petrova; N. V. Permyakova; I. R. Grin; D. O. Zharkov (Вавиловский журнал генетики и селекции)
One of the main mechanisms of epigenetic regulation in higher eukaryotes is based on the methylation of cytosine at the C5 position with the formation of 5-methylcytosine (mC), which is further recognized by regulatory proteins. In mammals, methylation mainly occurs in CG dinucleotides, while in plants it targets CG, CHG, and CHH sequences (H is any base but G). Correct maintenance of the DNA methylation status is based on the balance of methylation, passive demethylation, and active demethylation. While in mammals active demethylation is based on targeted regulated damage to mC in DNA followed by the action of repair enzymes, demethylation in plants is performed by specialized DNA glycosylases that hydrolyze the N-glycosidic bond of mC nucleotides. The genome of the model plant Arabidopsis thaliana encodes four paralogous proteins, two of which, DEMETER (DME) and REPRESSOR OF SILENCING 1 (ROS1), possess 5-methylcytosine-DNA glycosylase activity and are necessary for the regulation of development, response to infections and abiotic stress and silencing of transgenes and mobile elements. Homologues of DME and ROS1 are present in all plant groups; however, outside A. thaliana, they are poorly studied. Here we report the properties of a recombinant fragment of the ROS1 protein from Nicotiana tabacum (NtROS1), which contains all main structural domains required for catalytic activity. Using homologous modeling, we have constructed a structural model of NtROS1, which revealed folding characteristic of DNA glycosylases of the helix– hairpin–helix structural superfamily. The recombinant NtROS1 protein was able to remove mC bases from DNA, and the enzyme activity was barely affected by the methylation status of CG dinucleotides in the opposite strand. The enzyme removed 5-hydroxymethylcytosine (hmC) from DNA with a lower efficiency, showing minimal activity in the presence of mC in the opposite strand. Expression of the NtROS1 gene in cultured human cells resulted in a global decrease in the level of genomic DNA methylation. In general, it can be said that the NtROS1 protein and other homologues of DME and ROS1 represent a promising scaffold for engineering enzymes to analyze the status of epigenetic methylation and to control gene activity.